Passing the ICT skills test - Ferrigan, Clive, (Achieving QTS., 2011)
All trainee teachers hoping to gain Qualified Teacher Status need to pass a computerised ICT skills test. This book outlines the test requirements and explains the basic subject knowledge essential to completing the test.